Aligned Polythiophene and its Blend Film by Direct‐Writing for Anisotropic Charge Transport. (22nd May 2014) - Lu, Guanghao; Chen, Jiayue; Xu, Wentao; Li, Sijun; Yang, Xiaoniu
<x xml:space="preserve">Abstract</x> A combination of patterning and film alignment techniques helps to build multi‐order polymer architecture for application in flexible electronics. A direct‐writing method is employed using microcapillary arrays to prepare semiconducting polymer films with both optical and electrical anisotropy. Not only aligned poly(3‐butylthiophene) (P3BT) nanowires in neat P3BT films, but also aligned P3BT nanowires within a polystyrene (PS) matrix are obtained, which yields an aligned semiconductor/insulator polymer blend with anisotropic charge transport. The field‐effect transistor (FET) mobilities/threshold voltages from both vertical and parallel to alignment directions as well as their dependence on blending ratio are studied. The increased mobility of P3BT/PS blends, as compared with neat P3BT, is observed in both vertical and parallel directions. Using this alignment method, FET mobility and threshold voltage of the semiconductor/insulator polymer blends are comprehensively tuned, from which a digital inverter with gain up to 80 is realized. Therefore, this work not only helps understanding the charge transport mechanism in semiconducting/insulating polymer blends, but also provides an effective approach towards high‐performance field‐effect transistors with tunable mobility and threshold voltage.